Ice volumes in permafrost landscapes of Arctic Yakutia - Fedorov, Alexander N.; Konstantinov, Pavel Y.; Vasiliev, Nikolay F.; Basharin, Nikolay I.; Shepelev, Andrei G.; Andreeva, Varvara A.; Semenov, Valerii P.; Torgovkin, Yaroslav I.; Desyatkin, Alexey R.; Zheleznyak, Mikhail N.; Semiletov, Igor P. (Land)
This article is devoted to the study of the distribution of ground ice volumes in the upper layers of 5–10 m permafrost in the permafrost landscapes of Arctic Yakutia. Compilation of such a map will serve as a basis for assessing the vulnerability of permafrost to global warming, anthropogenic impact and forecasting the evolution of permafrost landscapes. The map was compiled using ArcGIS software, which supports attribute table mapping. The ground ice map of Arctic Yakutian permafrost landscapes shows that about 19% of the area is occupied by ultra ice-rich (above 0.6 in volumetric ice content) sediments. Very high ice volumes (0.4–0.6) are cover approximately 27%, moderate ice volumes (0.2–0.4)—25% of the area, and low ice volumes (less than 0.2)—about 29% of Arctic Yakutia.